2019
DOI: 10.1101/809061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interdependent Allosteric FFA2R Modulators Synergistically Induce Functional Selective Activation and Desensitization in Neutrophils

Abstract: The non-activating allosteric modulator AZ1729, specific for free fatty acid receptor 2 (FFA2R), transfers the orthosteric FFA2R agonists propionate and the P2Y2R specific agonist ATP into activating ligands that trigger an assembly of the neutrophil superoxide generating NADPH-oxidase. The homologous priming effect on the propionate response and the heterologous receptor cross-talk sensitized ATP response mediated by AZ1729 are functional characteristics shared with Cmp58, another non-activating allosteric FF… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…A tentative binding/signaling/activation-model, postulating three receptor binding sites in FFAR2 is presented. This model is based on data showing that the non-activating allosteric FFAR2 modulators AZ1729 and Cmp58 interdependently activate neutrophils to produce/release superoxide (O2 -), and that the signaling profile downstream of the receptor is biased (10) in that no transient rise in intracellular Ca 2+ is triggered during this activation of FFAR2. Neutrophil activation by orthosteric FFAR2 agonists is modulated in the same way by the non-activating compounds Cmp58 and AZ1729 but the enhanced response is achieved through binding of the two modulators to distinctly different allosteric receptor sites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A tentative binding/signaling/activation-model, postulating three receptor binding sites in FFAR2 is presented. This model is based on data showing that the non-activating allosteric FFAR2 modulators AZ1729 and Cmp58 interdependently activate neutrophils to produce/release superoxide (O2 -), and that the signaling profile downstream of the receptor is biased (10) in that no transient rise in intracellular Ca 2+ is triggered during this activation of FFAR2. Neutrophil activation by orthosteric FFAR2 agonists is modulated in the same way by the non-activating compounds Cmp58 and AZ1729 but the enhanced response is achieved through binding of the two modulators to distinctly different allosteric receptor sites.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note, that the allosterically modulated FFAR2s were able to signal through different G-proteins containing either Gai or Gaq subunits ("induced-bias" (12,13)). Based on earlier findings, it is reasonable to assume that FFAR2 has multiple ligand binding sites allowing different allosteric modulators to distinctly affect the affinity/efficacy of orthosteric ligands; we recently showed that AZ1729 lacks direct activating effects in its own but turns the natural FFAR2 agonist propionate into a potent activator of the neutrophil NADPH-oxidase, and that neutrophils are activated by the non-activating modulator AZ1729 when combined with another non-activating allosteric modulator, Cmp58 (10). The novel activation/sensitization mediated by the two allosteric FFAR2 modulators was reciprocal, and represented a new regulatory mechanism that controls GPCR signaling.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The copyright holder for this preprint (which was this version posted March 8, 2019. ; https://doi.org/10.1101/571604 doi: bioRxiv preprint To further explore Act-389949 mediated GPCR cross-talk in human neutrophils, we determined the Act-389949 induced neutrophil response in the presence of an FFA2R (free fatty acid receptor 2) specific allosteric modulator [54]. This allosteric modulator (Cmp58) has been shown to prime neutrophils for the responses induced by low concentrations of FPR agonists, a priming achieved through a novel receptor cross-talk mechanism [54,55]. In accordance with published data, the NADPH-oxidase activity induced by low nanomolar concentrations of Act-389949 in neutrophils pre-incubated with the allosteric FFA2R modulator was also augmented compared to the response in naïve neutrophils (Fig 6C).…”
Section: Act-389949 Co-operates With Other Gpcr Agonists and Modulates The Neutrophil Nadphoxidase Activity Through Receptor Cross-talk Mmentioning
confidence: 99%